Media in the News: How Australia's Media Beat Covered Two Major Journalism Change Events. (7th February 2023) - Zion, Lawrie; Sherwood, Merryn; O'Donnell, Penny; Marjoribanks, Timothy; Ricketson, Matthew; Dodd, Andrew; Deuze, Mark; Buller, Bradley
ABSTRACT: As the primary mechanism through which journalistic labour is organized within a newsroom, news beats are an important feature of journalistic research. However, within the extensive research that examines beat reporting and its specialties, there is little that examines how the media covers itself—or the media beat. This study explores the media beat in Australia, examining how media covered two major media change events: the loss of jobs at newspaper publisher Fairfax in 2012 and the potential closure of wire service Australian Associated Press (AAP) in 2020. In analysing reporting of change events in journalism through a framework of metajournalistic discourse, and through an analysis of 200 items, this study found that "media beat' journalists included more information about the adverse effects of job loss and disruption on news supply in 2020 than in 2012. Intermedia competition often shaped coverage, with journalists reporting change in rival media companies. Yet, how "media beat" reporters covered these changes varied in both years. The study also found that stakeholders from within and outside of media contribute to the development of change narratives in journalism by offering robust discussion of the implications of industry transformation for news quality and informed publics.